2012
DOI: 10.1371/journal.pone.0049249
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MACC1 Transcripts in Colorectal Cancer Patient Plasma Predict Metastasis and Prognosis

Abstract: BackgroundMetastasis is the most frequent cause of treatment failure and death in colorectal cancer. Early detection of tumors and metastases is crucial for improving treatment strategies and patient outcome. Development of reliable biomarkers and simple tests routinely applicable in the clinic for detection, prognostication, and therapy monitoring is of special interest. We recently identified the novel gene Metastasis-Associated in Colon Cancer 1 (MACC1), a key regulator of the HGF/Met-pathway. MACC1 is a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 40 publications
3
63
0
3
Order By: Relevance
“…Most investigations of the role of MACC1 in cancer progression focused on the mechanism whereby MACC1 promotes metastasis in a variety of cancers [16,17,18,19,20,21,22]. The present study attempted for the first time to explore its role in mediating cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most investigations of the role of MACC1 in cancer progression focused on the mechanism whereby MACC1 promotes metastasis in a variety of cancers [16,17,18,19,20,21,22]. The present study attempted for the first time to explore its role in mediating cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…MACC1 regulates cell proliferation by modulating the transcription of MEF, the receptor of hepatocyte growth factor HGF [296]. Similarly to this study, strong upregulation of the HOTAIRM1 lncRNA was also observed.…”
Section: Nervous System Development and Function Tissue Morphology supporting
confidence: 85%
“…MACC1, HGF/MET sinyal yolağının etkinleşmesi üzerinden tümör gelişimi ve yayılımının anahtar bir düzenleyicisi olarak görev alır (5,6). Hücre çoğalması, hareketlilik, nüfus edebilirlik ve yayılımı sağlamak için epitelyal-mezenkimal geçişte önemli bir rol oynar (5,7).…”
Section: Introductionunclassified
“…Hücre çoğalması, hareketlilik, nüfus edebilirlik ve yayılımı sağlamak için epitelyal-mezenkimal geçişte önemli bir rol oynar (5,7). MACC1 proteini bir transkripsiyon faktörü olarak işlev görür ve reseptör tirozin kinazların (Met) özendirici bölgelerine (promoter) bağlanır (5)(6)(7)(8). Met'in transkripsiyon etkinliğini uyarmak için esas olan, Met özendirici bölgesi üzerinde özel Sp1 bağlanma bölgelerinin 60 bç yakınına bağlanır ve HGF/c-Met uyarı yolağının etkinliğini uyarır ve hücre çoğalmasını, hareketliliğini ve yayılımı arttırır (9).…”
Section: Introductionunclassified
See 1 more Smart Citation